THE PRESENCE OF ABSENCE: Michael Reisch's and Andreas Gefeller's Impossible Realities. (4th May 2019) - Breede, Laura
Abstract : The photo artists Michael Reisch and Andreas Gefeller are visualizing environments, man-made landscapes and architectural surroundings that could be perceived as standing in the tradition of documentary landscape and architectural photography or as being created for scientific use. Subtle visual shifts provoke moments of confusion and exceed the physical possibilities of the viewer's perception in an imaginable extra-pictorial reality. By examining interlacing levels of realities — evoked by picture editing processes of digital and analog photographs — these phenomena will be denominated as Impossible Realities. Both artists practice perplexing "games" with distance and nearness, perceptible "mistakes" and seemingly "hygienic" views, leading viewers to doubt the authenticity — in terms of being not manipulated — of the photographs. The subjects hover between apocalyptic doubts and utopian perceptions of the ideal, stimulating reflections on preshaped ideas and concepts of pure nature, on human-influenced environmental changes and the charged relationship between urban environments and seemingly unspoiled nature (the very present sense of human absence plays an important role). Through the photographic process and the postproduction the images as ideas/imaginations and as material become hybrid constructions that could symbolically stand for the impossible but imaginable realities both artists evoke, varying between documentation and imagination.